G432(P) Development of symptom assessment service at a children's hospice. (12th March 2018) - Balfe, JM; Cassidy, M; Booth, A
Abstract : Background and aims: High symptom burden has been recognised in children with life-limiting conditions (LLC) and symptom assessment and management is a core component of children's palliative care (CPC). A previous audit highlighted a high prevalence of problematic symptoms in children accessing the hospice service prompting the development a symptom management team led by a paediatric consultant and CNS in CPC in spring 2016. All children in the earlier audited were in ACT category 3 and 4 and had diagnoses of severe disability with associated complex medical needs. This report aims to describe the development of the service and provide data from the first year's activity. Methods: A record of all referrals to the team has been maintained since its inception. A retrospective chart review was performed and data was collected and recorded on an excel spreadsheet. Data recorded included description of problematic symptoms, team members involved and intervention required. Results: Referrals to the team are accepted from nursing and healthcare staff involved in the care of the child. A care pathway, symptom assessment tools and symptoms management plans have been developed. To date 39 children have received support from the team, 7 of the children have died since referral. The CNS, wider nursing and multi-disciplinary team have supported all children referred. Medical assessment has been provided to 30 children. 25 children were offered a short break in the hospice to allow careful evaluation of symptoms using formal symptom assessment tools. All children were provided with a symptom management plan and on-going support, at home, in the hospice or by telephone, individualised according to identified need. Parental and healthcare professional feedback has been positive. Conclusion: This report describes the initial establishment of a symptom assessment service in a children's hospice. The service has been developed in recognition of the high burden of problematic symptoms in children with severe disability and complex medical needs. It is anticipated that the service will continue to develop to meet the increasing needs of children with LLCs.